Analisis Strategi Penjualan Dalam Meningkatkan Penjualan Barang Dimasa Pendemi Covid-19 Pada PT. Andalan Bintang Sampali - Silitonga, Rongga; Wahyuni, Dewi (UNIVERSITAS DHARMAWANGSA, 2023)
To create a sales strategy for PT. Andalan Bintang Sampali must know the appropriate market share during Covid-19, and be accompanied by customer needs. If PT. Andalan Bintang Sampali implements a strategy to sell goods that is not in line with market share, so what has been done could be in vain. And things like that must be avoided, because the strategy for selling goods is useful for increasing sales volume. The problem in this research is to analyze the strategy for selling goods in increasing sales during the Covid-19 pandemic at PT. Mainstay Bintang Sampali. The type of research used is descriptive research, namely research carried out by collecting, compiling, analyzing and designing strategies for selling goods to increase sales during the Covid-19 pandemic at PT. Mainstay Bintang Sampali. The results of the research concluded that the strategy for selling goods is through components products implemented very well by PT. Bintang Sampali's mainstay in increasing sales volume during the Covid-19 pandemic is by selling goods that are complete needs of the community in building houses. The strategy of selling goods through price components is implemented very well by PT. Bintang Sampali's mainstay in increasing sales volume during the Covid-19 pandemic is by providing the best prices that can be reached by all groups, and always providing attractive promotions every day. The strategy of selling goods through distribution channels is implemented very well by PT. Bintang Sampali's mainstay in increasing sales volume during the Covid-19 pandemic is by choosing a place or location based on the strategic location so that it is easily accessible to consumers, and based on the stock capacity of goods. Highways with easy access, spacious parking lots and spacious goods warehouses making it easier for company operations to distribute goods ordered by consumers.Keyword: Strategy, Sales, Covid -19